Financing in Inclusive Education : Opportunities and Challenges in Islamic Higher Education Institutions - Amir, Faizal; Raharjo, Tri Joko; Formen, Ali (Proceedings of International Conference on Science, Education, and Technology, 2025)
Inclusive education has become a global commitment to ensuring equitable and accessible education for all, including marginalized groups and individuals with disabilities. in realizing this goal, financing remains one of the major challenges, particularly within Islamic higher education institutions. This study aims to explore both the opportunities and constraints in financing inclusive education in Islamic universities and colleges. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and document analysis at selected Islamic higher education institutions. The findings reveal that limited internal budgets, dependency on tuition fees, and the underutilization of Islamic social funds such as zakat and waqf are among the key obstacles to implementing inclusive education. Nevertheless, significant opportunities exist through the strategic use of Islamic philanthropic resources, external partnerships, and the strength of institutional capacity for sustainable financing. This study recommends the development of strategic financial planning rooted in Islamic values and the principles of social justice to enhance inclusive education systems in Islamic higher education.